Technical report: approximating the length of California Halibut (Paralichthys Californicus) using Euler's and second order Runge-Kutta methods / Ili Suhaili Mohd Saman, Nur Shazlina Mohamad Shahril and Nabilah Nazurah Anuar - Mohd Saman, Ili Suhaili; Mohamad Shahril, Nur Shazlina; Anuar, Nabilah Nazurah (2016)
According to California Department of Fish and Wildlife, said California halibut is one of the most important commercial and recreational species in southern California. California halibut are the target of a strong statewide commercial fishery. There are three principle gear types used in the fishery are hook-and-line, trawl, and set gill net. Once landed, halibut are sold as fresh fillets or in live conditions to the restaurants or fish markets. Most halibut are consumed domestically with very few going to export. Annual commercial landing of halibut have averaged over 1 million pound over the past 8 years. Thus, this study embarks on considered the equation of population dynamics and interacting growth of California halibut. There are (3) main objectives for this study. Firstly, the study is conducted to estimate the length of California halibut in the age of range I to 10 years. Secondly is to comparing real data with Euler's method and Second Order Runge-Kutta method (RK2). Finally, the study is also done to determine the "suitable" approach method by analyze and comparing error that represented by each method with real data. The objective function of Euler's method and Second Order Runge-Kutta method (RK2) for measure California halibut is to know the approximating the increases growth length according time. The real data are obtained from University of California. Based on result found, the growth length of fish increases according to time. Study discovered that Second Order Runge-Kutta method (RK2} is the suitable approach for determining the growth length of the fish. The method and findings of the solution are hoped to be able to provide useful information to recreational and commercialize California halibut fishery.